Nitrogen use by standard height and semi-dwarf barley isotypes - Nedel, Jorge Luiz; Edward Ullrich, Steven; Lee Pan, William (Pesquisa Agropecuaria Brasileira, 1997)
Considering that a substantial amount of N applied in cereal production may be lost by leaching or erosion, the development of cultivars with increased efficiency to utilize N and more efficient N management practices are desirable. The objective of this experiment was to study the effect of 30, 60, 90 and 120 kg of N/ha on N use by four standard height semi-dwarf normal-mutant malting barley isotype pairs (Morex, Hazen, Norbert, Andre). Genotypic differences in N remobilization in the grain, remobilization efficiency, utilization efficiency and uptake efficiency and N use efficiency were observed. The standard isotypes with few exceptions had higher values for all of these N traits. Nitrogen remobilization in the grain increased with increasing N fertilization while N utilization and N use efficiency decreased in both standard and semi-dwarf isotypes. Nitrogen use and grain yield relations are discussed.
Keywords: Hordeum vulgare; nitrogen remobilization; nitrogen efficiency